2017
DOI: 10.1111/acer.13371
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Stability of Heavy Drinking Days and Drinking Reductions Among Heavy Drinkers in the COMBINE Study

Abstract: Background Recently, the Food and Drug Administration (FDA) proposed to expand the options for primary endpoints in the development of medications for alcohol use disorder (AUD) to include either abstinence from alcohol or a non-abstinent outcome: no heavy drinking days (with a heavy drinking day defined as more than 3 drinks per day for women and more than 4 drinks per day for men [>3/>4 cutoff]). The FDA also suggested that 6 months would be the most appropriate length for a clinical trial to demonstrate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
4
16
0
Order By: Relevance
“…However, other analyses found that the likelihood of maintaining moderate drinking was lower in severely dependent patients (more than 6 dependence criteria out of 9 [DSM-IIIR]) [44], which is consistent with several other studies showing that moderate drinking goals might be most appropriate for individuals with lower levels of AD severity [45,46,47]. Similarly, a recent secondary analysis of the COMBINE study data showed stability of no heavy drinking as an outcome within the first 4 months of treatment [48]. …”
Section: Examining Reduced Alcohol Consumption In Treatment Trials Ansupporting
confidence: 78%
“…However, other analyses found that the likelihood of maintaining moderate drinking was lower in severely dependent patients (more than 6 dependence criteria out of 9 [DSM-IIIR]) [44], which is consistent with several other studies showing that moderate drinking goals might be most appropriate for individuals with lower levels of AD severity [45,46,47]. Similarly, a recent secondary analysis of the COMBINE study data showed stability of no heavy drinking as an outcome within the first 4 months of treatment [48]. …”
Section: Examining Reduced Alcohol Consumption In Treatment Trials Ansupporting
confidence: 78%
“…In addition, they may be almost free of negative consequences of heavy drinking also in just 4 weeks of treatment, and maintain this almost absence of negative consequences throughout the 12 weeks of treatment. And this would be in accordance with a secondary analysis of the COMBINE study showing stability of no heavy drinking (Witkiewitz et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the treatment period for COMBINE was 16 weeks, however only the first 12 weeks of data were analyzed in the current paper. Recent work examining the COMBINE data has indicated that most changes in drinking occur during the first 2–3 months of treatment[50], which is reflected in the time-period analyzed in the current study. Nonetheless, future research examining the full 16 week treatment period could further help elucidate predictors of drinking patterns during treatment in the COMBINE study.…”
Section: Discussionmentioning
confidence: 92%